2013
DOI: 10.1128/jb.01121-12
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Escherichia coli FeoA and Its Potential Role in Bacterial Ferrous Iron Transport

Abstract: Iron is an indispensable nutrient for most organisms. Ferric iron (Fe 3؉) predominates under aerobic conditions, while during oxygen limitation ferrous (Fe 2؉ ) iron is usually present. The Feo system is a bacterial ferrous iron transport system first discovered in Escherichia coli K-12. It consists of three genes, feoA, feoB, and feoC (yhgG). FeoB is thought to be the main transmembrane transporter while FeoC is considered to be a transcriptional regulator. Using multidimensional nuclear magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 77 publications
(138 reference statements)
8
57
0
Order By: Relevance
“…The role of FeoA is not well defined, even though it is present in the majority of organisms that contain a Feo system (31). We investigated the role of FeoA in FeoB complex formation by mutational analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of FeoA is not well defined, even though it is present in the majority of organisms that contain a Feo system (31). We investigated the role of FeoA in FeoB complex formation by mutational analysis.…”
Section: Discussionmentioning
confidence: 99%
“…FeoA is a small hydrophilic protein whose role is unknown, but it has been shown to be required for Feo function in several bacterial species (27)(28)(29). FeoA shows structural similarity to an Src-homology-3 (SH3) domain fold, suggesting that FeoA may mediate proteinprotein interactions (26,(30)(31)(32). FeoA was shown to interact with FeoB in a bacterial two-hybrid (BACTH) assay in Salmonella enterica (29).…”
mentioning
confidence: 99%
“…The feo operon from gammaproteobacteria encodes 3 proteins: FeoA, FeoB, and FeoC (11)(12)(13). FeoA, present in 90% of the feo operons, is a small Src homology 3 (SH3) domain protein necessary for ferrous iron transport (6,12,(14)(15)(16). Recent enzymatic assays have suggested that FeoA may not act as a GTPase-activating protein as originally proposed (14).…”
mentioning
confidence: 99%
“…FeoA, present in 90% of the feo operons, is a small Src homology 3 (SH3) domain protein necessary for ferrous iron transport (6,12,(14)(15)(16). Recent enzymatic assays have suggested that FeoA may not act as a GTPase-activating protein as originally proposed (14). FeoB, an indispensable component of the Feo system, is a large protein consisting of an intracellular amino-terminal domain (NFeoB) and a transmembrane carboxyl-terminal domain presumed to form the Fe 2ϩ pore function that functions as a permease.…”
mentioning
confidence: 99%
“…This gene is part of the Feo system, which has the function of transporting ferrous iron and has been associated with virulence in E. coli, Helicobacter pylori, Legionella pneumophila and Campylobacter jejuni [22]. Iron uptake appears to be one of the main virulence factors in strains of APEC.…”
Section: Discussionmentioning
confidence: 99%